Impact of Technological Parameters of CO2 Laser Cutting on oxide adhesion forces on the Base Material - Zrak, Andrej; Tofil, Szymon; Šutka, Jozef; Moravec, Ján (Manufacturing Technology Journal, 2019)
The setting of laser cutting technology parameters affects the resulting state of the final surface. When cutting low-carbon steel using conventional parameters - oxidative cutting, surface oxide layers are formed on the cutting edges resulting from an exothermic reaction by burning material. The oxide layers are undesirable and can cause complications if the components so produced are further coated. The color coat creates an adhesion layer on the surface oxide, and when the oxide has low adhesion to the base material, the paint drops out of the surface with the oxide. Mechanical removal of oxide by grinding, punching or brushing is another manufacturing operation that causes an increase in the cost of production. Chemical cleaning is, in turn, detrimental to workers and is also a burden on the environment. For chemical purification of oxides, phosphoric acid and the like are used. The paper describes cutting low-grade steels in a way that does not require removal of oxides and adhesion bonding between the component and the color coating is sufficient for the use of the component in operation.
Keywords: Laser cutting; quality of cutting surface; surface oxide; adhesive forces; color coatings